PENGEMBANGAN QR CODE SCANNER BERBASIS ANDROID UNTUK SISTEM INFORMASI MUSEUM SONOBUDOYO YOGYAKARTA - Bambang Sugiantoro (Telematika, 2015)
Along with the development of smartphone technology, the museum as an asset of the government also had to adjust the display collection. QR Code Scanner application built using Android-based ZBar Library features the Scanner, Bookmark, about Sonobudoyo, and display photos in 3D Rotate collection. All features in these applications can be run properly. Results of alpha testing is all in the application process successfully run during testing. Beta testing the application functionality obtained 100% of respondents said "Yes", and 0% of respondents said "No". While beta testing the system interface with the score is 66.4 which is located on the rating scale between 54.41 - 67.20 is satisfied